2018
DOI: 10.1177/0956462418799181
|View full text |Cite
|
Sign up to set email alerts
|

Empiric antimicrobial treatment for asymptomatic sexual contacts of sexually transmitted infection in the era of antimicrobial resistance: time to rethink?

Abstract: Prudent prescribing of antimicrobials is essential in ameliorating the public health problem of antimicrobial resistance. This retrospective audit assesses whether empiric antimicrobial treatment for asymptomatic sexual contacts of sexually transmitted infection is appropriate based on laboratory confirmation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 4 publications
1
33
0
Order By: Relevance
“…A recent Australian study looking at EAT in asymptomatic contacts of STIs found that the majority of patients received inappropriate treatment in retrospect. 6 This finding led the researchers to discontinue empirical antibiotics for asymptomatic contacts.…”
Section: Resultsmentioning
confidence: 99%
“…A recent Australian study looking at EAT in asymptomatic contacts of STIs found that the majority of patients received inappropriate treatment in retrospect. 6 This finding led the researchers to discontinue empirical antibiotics for asymptomatic contacts.…”
Section: Resultsmentioning
confidence: 99%
“…Such epidemiological treatment of asymptomatic sexual contacts for infections such as gonorrhoea and Chlamydia is now being challenged if confirmed infection rates are low, and in the current climate of antibiotic stewardship and quicker turnaround of accurate test results. [22][23][24] One recent audit from Sydney found only seven confirmed cases among 59 asymptomatic MSM reporting sexual contact with Chlamydia. 23 Point-of-care or real-time NAATs that provide accurate results on the same day as testing are on the horizon for many services and have the potential to significantly reduce unnecessary epidemiological treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] One recent audit from Sydney found only seven confirmed cases among 59 asymptomatic MSM reporting sexual contact with Chlamydia. 23 Point-of-care or real-time NAATs that provide accurate results on the same day as testing are on the horizon for many services and have the potential to significantly reduce unnecessary epidemiological treatment. 24,25 Testing protocols for genital ulcers among high-risk patients such as many MSM will need revision to avoid misdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…A 2017 single centre audit in Australia of 100 asymptomatic contacts of STIs was undertaken on a very different population consisting of 97% MSM or bisexual men. 19 59 patients reported contact with chlamydia but only 7 had a confirmed NAAT diagnosis giving a prevalence of 12% in contacts, and the clinic has subsequently halted its use of empiric antibiotics for the treatment of STI contacts.…”
Section: Discussionmentioning
confidence: 99%